Family functioning, psychological distress and suicidal tendencies among adolescents in Ghana - Mawuko Setordzi; Samuel Adjorlolo (South African Journal of Psychiatry, 2025)
Background: Adolescence is characterised by profound changes in physical, cognitive, emotional and social functioning and is associated with psychological distress and suicidal tendencies. The family plays a significant role in safeguarding and promoting adolescents’ mental health. However, little is known about the influence of family functioning on adolescents’ psychological distress and suicidal tendencies in Ghana.